Generativity and Talents in Times of Transition - Tomarchio, Maria; Tessaro, Fiorino; Strongoli, Raffaella; Gentile Margiotta, Margherita; Dozza, Liliana (Formazione & insegnamento, 2025)
Asking what counts as talent in an age of transitions means detaching it from the notion of a gift and reframing it as a stance that takes shape at the nexus of capabilities, relationships and opportunities. Following Umberto Margiotta, this editorial traverses the lexicon of educational justice, the quality of environments and communities, the stewardship of time—between chronos and kairos—and the reflective use of technologies (up to and including AI) to show how educational contexts can continue to serve as transformative horizons. From this, several lines of work emerge: designing spaces that integrate knowledge and ties with local communities, safeguarding the rhythms of experience, recognising and strengthening capabilities across the life course, and conceiving assessment and guidance as practices of recognition. The aim is to activate generative environments, inhabit time with authenticity, and renew professional responsibilities so that plural talents can flourish.